(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Material and methods. There were 34(68 eyes) children at the age of 8–14 under observation. Among them there were children with myopia of mild degree (7), moderate degree (10), and high degree (7) as well as a control group healthy of children of the same age — 10 people. Visometry, ophthalmometry, refractometry in conditions of cycloplegia biomicroscopy and ophthalmocopy were made in all patients. Free and connected SH and S-S — groups in the tear fluid were determined by spectrocolormeter Spekol-210 with a wave length of 356 nm and 412 nm accordingly. Results. It was established that in average values of connected SH and S-S — groups’ levels in the tear fluid had no significant difference in comparison with values in healthy children but it was found that SS — free and connected groups had the tendency to increase in average by (4.8–14.5) % depending on the myopic degree. Free SH- groups content in tear of children with high myopia was lower in comparison with the control group by 28 % (54. 2 ± 5.5) units, p<0.05. Conclusions 1. Studies of SH- content in the tear fluid have shown that the level of antioxidant protection in myopia depends on its degree: the higher degree, the lower is the concentration of free SH-groups, and the lower level of antioxidant protection. 2. The tendency is noticed of the free and connected S-S-groups levels increase in the tear by (4.8 -14.5) % with degree of myopia that is evidence of the decrease of detoxic protection in these patients. 3. Significant decrease in the concentration of the SH — groups (by 28 %) in the tear fluid in children with myopia of high degree in comparison with healthy children speaks about disorder of the protective antioxidant system.